Suppose and are two roots of the above equation. Find the value of .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Note that if a and b are negative, then a b = a b . Let a = − m and b = − n where m and n are positive. Now a b = m n and hence a b = − m − n = ( i m ) ( i n ) = − m n = a b .
By Vieta's formula, we have a + b = − 7 0 and a b = 1 4 4 . In this case, a and b are negative.
Now ( a + b ) 2 = ( a ) 2 + 2 a b + ( b ) 2 = a + b − 2 a b = − 7 0 − 2 ( 1 2 ) = − 9 4 .